CIRCUITO DE ATIVIDADES MOTORAS NA EDUCAÇÃO INFANTIL: UMA REFLEXÃO PEDAGÓGICA - Polanczyk, Marcelo B.; Nascimento, Marcelo B. d.; Fenner, Daiana d. S.; Silva, Aron I. d.; Vargas, Daiana (Salão do Conhecimento, 2013)
Resumo